Exploring the synergy of neuroleadership and Islamic values in shaping Generation Z leaders: A mixed method analysis - Irhamni, Muhammad Ricza; Putri, Linda Indiyarti; Aamir, Mahrukh; Afnizar, Ikmal (University of Islam Malang, 2024)
The synergy of neuroleadership and Islamic values is crucial in addressing leadership challenges posed by Generation Z, particularly in combating toxic leadership, negative culture, and turnover. Generation Z's unique behaviors require leaders who combine neuroleadership and Islamic values to inspire and create positive environments. However, a lack of studies in Indonesia, the largest Muslim-majority country, highlights a significant research gap. Using a mixed-method approach, this study investigates how Islamic values and neuroleadership influence leadership skill development. We conducted focus group discussions with 60 participants and surveyed 317 active members of the biggest Islamic organization in Indonesia, aged 17–23, to test the hypotheses. The results show that both neuroleadership and Islamic values affect leadership skills. Among the eight neuroleadership indicators, transfer and caring are the most influential in shaping leadership skills. Additionally, in accordance with Islamic values, fairness and tolerance are key factors for effective leadership. Generation Z seeks to be heard and understood. While they may lack problem-solving skills, they excel in fairness, tolerance, and relationships.